Primary Care English - Ribes, Ramón; Garcia Gimeno, Isabel; Jones, Roger (Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book is for those family doctors and any other health care professionals involved in Primary Care around the world who really want to make useful progress in their medical English, in order to be able to read and write articles, participate in international courses and meetings, read textbooks in their original English language and visit or work in an English speaking country to enrich their professional experience. If you are one of them, then this is the book you have been looking forward to. Here, theory and practice are carefully linked for optimal learning. This book has been written for you by doctors who understand your needs and who aim to help you get the most out of your learning experience, without wasting your valuable time. You will be able to learn just what you need and (almost) all you need to feel confident understanding and communicating in English within your speciality. Its revolutionary combination of formal teaching and conversational style, together with the selection of contents specific to Primary Care, will provide you with a unique platform to jump to a more advanced level with surprisingly little effort.